The control of small-scale syndepositional normal faults on sandstone distribution: example from the Paleogene bottom Sandstone Member in the Tabei Uplift, Tarim Basin, China - Xiaoyang, Gao; Luxing, Dou; Wenxiang, He; Qi, Sun; Zhenli, Yi; Bin, Li; Qiaolin, He; Jineng, Jin; Yong, Hu; Jingwen, Yan; Li, Zhang (Frontiers in Earth Science, 2025)
IntroductionThe syndepositional normal faults related paleogeomorphic units in sedimentary basins play a crucial role in controlling sediment transport and infill processes. Previous studies have primarily focused on the control of depositional systems by large-scale syndepositional faults. However, there is still a lack of systematic understanding about the control of intensively developed small-scale syndepositional normal faults on sandstone facies distribution in continental basin.MethodsThis study integrates 3D seismic data, well logs, and core descriptions to determine the depositional facies and small-scale syndepositional normal fault related paleogeomorphology are consistent during deposition of the Paleogene Bottom Sandstone Member of the WM7 fault zone area in the Tabei Uplift, Tarim basin.ResultsThe results indicate that the Paleogene Bottom Sandstone Member consists of deltaic sandstone facies and fine-grained lacustrine deposits containing evaporites near an erosional uplift. During the deposition of the Bottom Sandstone Member, an erosional uplift zone developed in the eastern part of the WM7 fault zone, where numerous incised valleys formed. In contrast, the fault zone and its western region were characterized by a delta–saline lake depositional system controlled by a syndepositional graben, with numerous small-scale en echelon syndepositional faults developing within the fault zone.DiscussionThese special geomorphic units composed of syndepositional faults were primarily formed by differential subsidence of strata. These faults and their associated paleogeomorphic units controlled the distribution characteristics of incised valleys and distributary channels. By analyzing the control exerted by micro - geomorphic units composed of syndepositional normal faults near the paleo-uplift on the distribution of sandstone, new insights are provided for predicting the distribution of sandstone in complex geomorphic units formed by small-scale syndepositional fault combinations in continental basins.